Shape grammars overview and assessment for transport and urban design: Review, terminology, assessment, and application - Vitins, Basil Janis; Axhausen, Kay (Journal of Transport and Land Use, 2016)
Shape grammars for urban design have attracted much interest in research and practice. Transport and urban planners increasingly deploy shape grammars, especially in simulations and procedural models. Shape grammars have multiple advantages due to their interdisciplinary and straightforward approach and low computational requirements. In addition, a rule-based design method and underlying fundamental research knowledge can potentially support future planning and design guidelines for handbooks and norms. However, little is known about the effectiveness of shape grammars in transport networks and urban environments. The proposed methodology aims at a future development of a robust and effective language for sustainable urban development. The theory of different fields is consolidated for a general grammar definition. Grammars require specified and corresponding objectives and application specifications for enhanced implementation. The proposed methodology for grammar rule assessment is based on elasticities to gain more insights in the effect of the rules. Elasticities allow comprehensive comparisons and verification between grammar rules. The paper reviews and highlights the key achievements and applications of shape grammars in cognate fields of science. Terminology sheds light on the definitions of most relevant terms including a general definition for grammar rules embedded in the language context. The paper differentiates methodological approaches in grammar design assessment and emphasizes a standardized approach for shape grammar definitions. The paper concludes with a detailed example for grammar rule assessment and potential future research.